Evolution of Concepts Related to the Term «Brand Reputation» and Their Relationship - Dinara Lenarovna, Kurbangalieva (2021)
Throughout the past decade, the theme of reputation has attracted growing interest in the world of corporate business. This interest is primarily due to the fact that reputation is beginning to have an increasing impact on the capitalization of brands. In addition, the accelerated development of information technology and the subsequent large-scale expansion of the organization into digital markets, with a new force, expanded the scientific field of research on the impact of intangible factors on the activities of brands. In numerous publications devoted to the study of the term reputation, both domestic and foreign researchers, there are different approaches to its definition. Previous analysis of works has shown that the reputation of an organization is often confused with the categories «brand», «brand image», «intangible assets», «goodwill» or «business reputation» (Malakhov, 2009), which have other nature and meaning. This article analyzes the views of various researchers of the above terms and, based on the work done, attempts to systematize these terms and offers the author's definition of the definition of «brand reputation».  This research will provide a theoretical basis for further research, namely, quantitative assessment of reputation in the era of market transformation and the spread of modern technologies.